The association between PD-L1 expression and the survival rate of patients with undifferentiated nasopharyngeal carcinoma - Indrawati; Auliya Suluk Brilliant Sumpono; Vivin Febriani; Kartika Widyawati Taroeno-Hariadi; Sagung Rai Indrasari; Camelia Herdini; Rheza Gandi Bawono; Ery Kus Dwianingsih (Published by Universitas Gadjah Mada, 2026)
Programmed cell death ligand-1 (PD-L1) plays a key role in tumor immune evasion. However, its prognostic significance in nasopharyngeal carcinoma (NPC) remains unclear. This study evaluated the association between PD-L1 expression and clinicopathological features and survival outcomes in patients with NPC. We conducted a retrospective analysis of 80 patients diagnosed with non-keratinizing undifferentiated NPC between 2015 and 2019. PD-L1 expression was assessed by immunohistochemistry using the 22C3 antibody and quantified as the tumor proportion score. Associations with clinicopathological variables were analyzed, and overall survival was evaluated using Kaplan–Meier and Cox regression analysis. PD-L1 expression was negative in 72.5% of cases, positive in 18.8% of cases, and strongly positive in 8.7% of cases. PD-L1 expression was not significantly associated with age, sex, disease stage, treatment modality, or overall survival (HR 1.71; p = 0.494). PD-L1 expression on tumor cells was not associated with clinicopathological characteristics or survival in non-keratinizing undifferentiated NPC. These findings suggest that PD-L1 alone is not a reliable prognostic biomarker for this NPC subtype, highlighting the need for integrated immune and molecular analyses in future studies.